2020
DOI: 10.21203/rs.3.rs-35654/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of an immune-related gene pair model to predict colon adenocarcinoma prognosis

Abstract: Background. Colon cancer is the most common type of gastrointestinal cancer and has high morbidity and mortality. Colon adenocarcinoma (COAD) is the main pathological type of colon cancer, and much evidence has supported the correlation between the prognosis of COAD and the immune system. The current study aimed to develop a robust prognostic immune-related gene pair (IRGP) model to estimate the overall survival of patients with COAD. Methods. The gene expression profiles and clinical information of patients w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…By acting on the immune checkpoints, it has been used to treat a variety of cancers, including sarcoma [16]. More importantly, previous studies indicated that immune-related genes (IRGs) can serve as an effective prognostic biomarkers in many tumors, such as urological cancer [17,18], digestive cancer [19][20][21][22] and non-small cell lung cancer [23][24][25][26]. Nonetheless, the role of IRGs in sarcoma remains unknown but urgent.…”
Section: Introductionmentioning
confidence: 99%
“…By acting on the immune checkpoints, it has been used to treat a variety of cancers, including sarcoma [16]. More importantly, previous studies indicated that immune-related genes (IRGs) can serve as an effective prognostic biomarkers in many tumors, such as urological cancer [17,18], digestive cancer [19][20][21][22] and non-small cell lung cancer [23][24][25][26]. Nonetheless, the role of IRGs in sarcoma remains unknown but urgent.…”
Section: Introductionmentioning
confidence: 99%
“…These results imply that different in ltration level of M0 Macrophages in different stages may play different roles in tumor progression. Luo et al found the increase of Tregs and M0 macrophages in COAD was correlated with worse clinical outcomes (27). In contrast, Forssell et al found that high macrophages in CC was associated with better patients' survival(28).…”
Section: Discussionmentioning
confidence: 99%